Fungal Community and Biodeterioration Analysis of Hull Wood and Its Storage Environment of the Nanhai No. 1 Shipwreck - Han, Yeqing; Huang, Xinduo; Wang, Yu; Du, Jing; Ma, Kaixuan; Chen, Yue; Li, Naisheng; Zhang, Zhiguo; Pan, Jiao (Frontiers in Microbiology, 2021)
The Nanhai No. 1 shipwreck is a Chinese merchant ship in the Southern Song Dynasty, and now it is stored in a huge enclosed glass warehouse in Maritime Silk Road Museum in Guangdong Province. At present, the hull of the Nanhai No. 1 shipwreck is still being excavated, and a small part of the hull wood is soaked in a specific solution to desalt. Through long-term exploration, we found that the above two states of hull wood had undergone biodeterioration, so the purpose of this study is to analyze the fungal community of exposed and soaked wood from the Nanhai No. 1 shipwreck. We sampled 10 exposed hull wood and sea mud samples, two wood storage water samples, and air samples in the glass warehouse. We used scanning electron microscope and optical microscope to find that there were obvious fungal structures in exposed wood and wood storing water samples. High-throughput sequencing of fungi revealed that the most abundant genera in exposed and soaked wood were Fusarium sp., and Scedosporium sp., respectively. In addition, Fusarium solani and Scedosporium apiospermum were successfully isolated from the hull wood surface and wood storing water samples, and the degradation tests of lignin and cellulose, the sensitivity tests of biocides and growth curve assay were carried out. We also found that Penicillium sp. and Cladosporium sp. are the most abundant in the glass warehouse air. Our research results show that F. solani and S. apiospermum should be regarded as a major threat to the preservation of the Nanhai No. 1 shipwreck. These results provide a reference for our protection of shipwrecks and other similar artifacts.